Case Report: Long-Term Tolvaptan Treatment in a Child With SIADH and Suprasellar Arachnoid Cyst - Puma, Andrea; Brugnara, Milena; Cavarzere, Paolo; Zaffanello, Marco; Piacentini, Giorgio; Gaudino, Rossella (Frontiers in Pediatrics, 2021)
Suprasellar arachnoid cysts represent a rare occurrence in the pediatric population and usually cause symptoms related to mass effect and can occasionally cause endocrine dysfunctions. The association between SAC and the syndrome of inappropriate antidiuretic hormone (SIADH) in the pediatric population has rarely been described previously. In most cases, SIADH is temporary and resolves by treating the underlying cause. The first-line treatment consists of fluid restriction in asymptomatic children. Oral urea and demeclocycline are other effective treatment options. Vaptans represent a relatively new class of medication for the management of SIADH. These agents are a nonpeptide vasopressin V2 receptor antagonist that selectively antagonizes the antidiuretic effect of AVP, resulting in excretion of diluted urine or “aquaresis”. Their efficacy has been shown in adult patients with euvolemic or hypervolemic hyponatremia. However, evidence is lacking in pediatric patients with SIADH. We report the case of a 9-year-old female child with a SAC, who underwent endoscopic fenestration at the age of 2 years. After surgery she developed chronic hyponatremia due to SIADH. Hyponatremia was refractory to treatment with fluid restriction, oral sodium and urea. In order to normalize serum sodium levels, tolvaptan treatment was started on a compassionate-use basis; 24-48 hours later serum sodium levels returned to normal. To date, tolvaptan has been used regularly for six years with no side effects occurring during the treatment period. This is the first case of a child with chronic SIADH secondary to SAC successfully treated with tolvaptan. Further studies are needed to demonstrate its usefulness on a broader case series.